(untitled) (Physical Education, Health and Social Sciences, 2024)
This study investigates the roles of coaching effectiveness and team unity in enhancing athlete performance among college-level athletes in Khyber Pakhtunkhwa, Pakistan. Data were collected from 1,660 male and 354 female athletes across various colleges. Descriptive statistics revealed a mean coaching effectiveness score of 4.2 (SD = 0.8) and a mean team unity score of 4.1 (SD = 0.7). Multiple regression analysis showed that coaching effectiveness (β = 0.51, p < 0.01) and team unity (β = 0.46, p < 0.01) significantly predicted athlete performance, accounting for 54% of the variance in performance (R² = 0.54). Structural Equation Modeling (SEM) confirmed the model’s fit with χ²(67) = 145.67, p < 0.01, RMSEA = 0.045, CFI = 0.97, TLI = 0.96, and SRMR = 0.032. The results validated that coaching effectiveness directly affects athlete performance and indirectly influences performance through team unity. These findings underscore the importance of effective coaching and strong team cohesion in optimizing athletic performance. The study suggests that sports programs should focus on both coaching development and team-building strategies to enhance performance outcomes. Keywords: Coaching Effectiveness, Team Unity, Athlete Performance, College Athletics & Sports Development